The Impact of Environmental, Social and Governance (ESG) Practices on the Financial Performance of Green Companies in Malaysia: An Empirical Analysis - Zainuddin, Zaemah; Abd. Wahab, Norazlina; Shari, Wahidah; Bahaman, Muhamad Abrar; Yusof, Rosylin Mohd; Abdul Karim, Norzitah (UI Scholars Hub, 2024)
This study examines the relationship between Environmental, Social, and Governance (ESG) perfor- mance and the financial performance of green companies in Malaysia. Analyzing 280 observations from 56 green companies listed in Bursa Malaysia from 2016 to 2020, the study employs rigorous regression analysis. The results indicate that ESG performance does not significantly influence the financial performance of these green companies. Instead, total sales and liability significantly impact both Return on Asset (ROA) and Return on Equity (ROE). These findings suggest that, despite the growing emphasis on ESG in the business sphere, other internal factors may have a more substantial effect on financial outcomes. While ESG considerations may not directly financial performance, their importance for social welfare and sustainable resource management remains indisputable.